Dissecting the Vesicular Trafficking Function of IFT Subunits - Yang, Huihui; Huang, Kaiyao (Frontiers in Cell and Developmental Biology, 2020)
Intraflagellar transport (IFT) is initially identified as a transport machine with multiple protein subunits, and is essential for the assembly, disassembly, and maintenance of cilium/flagellum, which serves as the nexus of extracellular-to-intracellular signal integration. To date, in addition to well-established and indispensable roles in ciliated cells, most IFT subunits have also shown more general roles of vesicular trafficking in non-ciliated cells. Thus, the purpose of this review is to summary the recent progress on vesicular trafficking functions of IFT protein and highlight the problems in future research.